The Role of The Village Administration in The Management of Tourist Village in Pacitan Regency - A. Hilman, Yusuf; Setyaningsih, Aprilia (MAJAPAHIT POLICY, 2022)
Jetak village is a village known as a tourist village because of its natural resources that can be managed into tourism. The purpose of this study is to formulate the role of the village government in tourism management and what are the supporting and inhibiting factors for tourism in Jetak village. This type of research is a qualitative research used to examine the condition of natural objects. The results of this study indicate that the role of the village government is to form village regulations on tourism, form Bumdes and channel funds. The supporting and inhibiting factors for tourism include the existence of natural resources that can be utilized, namely Pidakan and Watubale beaches, which can improve the community's economy. In addition to supporting factors, there are inhibiting factors in the form of limited funds in tourism development and management, because the village budget funds are not focused on tourism but are distributed to other needs such as assistance to the community. There is a decrease in the number of visitors.